Evaluation of Thyroidectomy Results Performed at a Tertiary Academic Center - Fatih Yunus Emre; Ersoy Doğan; Pembe Keskinoğlu; Merih Güray Durak; Sülen Sarıoğlu; Ahmet Ömer İkiz (Turkish Archives of Otorhinolaryngology, 2023)

(untitled)
Objective: The aim of the study was to retrospectively analyze the patients who underwent thyroidectomy at a tertiary academic center regarding their surgical indications, histopathological diagnosis, and surgical complications. Methods: The study included a total of 739 consecutive patients who underwent lobectomy, total thyroidectomy, or completion thyroidectomy performed under intraoperative nerve monitoring (IONM) at the Department of Otorhinolaryngology-Head and Neck Surgery of Dokuz Eylül University between January 2009 and December 2019. Demographic data of the patients, preoperative clinicopathological characteristics, postoperative complications, characteristics of surgery and histopathological results were evaluated. Results: There were 619 patients in the primary surgery and 120 patients in the revision surgery groups. Indications for surgery were suspicion of malignancy in 486, multinodular goiter in 214, and hyperthyroidism in 39 patients. Final histopathological evaluation of specimens revealed malignancy in a total of 507 (68.6%) patients. Rates of transient and permanent hypocalcemia were 7.3% (54/739) and 2.2% (16/739) in the whole group, while this was 6.6% (41/619) and 1.5% (9/619), respectively, among primary total thyroidectomy patients. There were 61 (8.3%) patients with transient recurrent laryngeal nerve (RLN) paralysis (unilateral in 60 patients, bilateral in one patient) and five (0.7%) patients with permanent unilateral RLN paralysis as postoperative complications. Rates for postoperative hematoma, seroma, wound infection and chylous fistula were 2.2%, 3.7%, 0.1%, and 0.5%, respectively. Conclusion: Our results support the safety of thyroid surgery performed under IONM in tertiary academic centers. Every institution should document and share its own results to properly inform its patients preoperatively.